Effect of dislocations on carrier recombination and photoelectrochemical activity in polished and unpolished TiO2 and SrTiO3 crystals - Zhang, Endong; Zhang, Mingxin; Kato, Masashi (Journal of Applied Physics, 2024)
TiO2 and SrTiO3 are stable and efficient materials for photoelectrochemical (PEC) water splitting. PEC activity is influenced by carrier recombination in crystals of these materials. In this study, we analyzed the effect of dislocations on carrier recombination in TiO2 and SrTiO3 using microwave photoconductive decay measurements on polished and unpolished faces. The apparent slow decay in the unpolished face implies that dislocations trap minority carriers. Based on the different dependences of the injected photon density and temperature, the recombination processes in the polished and unpolished faces differ. A high concentration of oxygen vacancies or hydroxyl in the unpolished face of SrTiO3 was observed by x-ray photoelectron spectroscopy, and dislocations in the unpolished faces of both materials were observed using transmission electron microscopy. Additionally, we found that the photocurrent duration in the unpolished faces was shorter than that in the polished faces for both TiO2 and SrTiO3, confirming that dislocations inhibited photoelectrochemical activity.
Created from Fastlane, Scopus look-up